Analisis Kualitas Website Desa Krandegan Terhadap Kepuasan Pengguna Dengan Metode Webqual 4.0 Dan End-User Computing Satisfaction (EUCS) - Nur Firmansyah, Rendy; Murhadi; Dewi Chirzah (P3M Politeknik Negeri Banjarmasin, 2025)
The advancement of information technology has encouraged the use of village websites as a means of digital public service. The Krandegan Village Website aims to deliver information and services to the community, but its quality needs to be evaluated in terms of user satisfaction. This study aims to analyze the influence of website quality on user satisfaction using the WebQual 4.0 and End-User Computing Satisfaction (EUCS) methods. WebQual 4.0 includes the dimensions of usability, information quality, and service interaction quality, while EUCS adds the timeliness dimension. This research employed a quantitative approach by distributing questionnaires to 100 website users. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4. The results indicate that usability (t-statistic = 4.987) and timeliness (t-statistic = 4.103) significantly affect user satisfaction. Meanwhile, information quality (t-statistic = 1.976) and service interaction quality (t-statistic = 2.214) also show positive but less significant effects. These findings highlight the importance of timely information updates and a user-friendly interface. Recommendations are given to improve website navigation, design, and service interaction to support a more responsive and effective digital public service system.